Design and ARM‐embedded implementation of a chaotic map‐based multicast scheme for multiuser speech wireless communication. (29th November 2016) - Gan, Qiuye; Yu, Simin; Li, Chengqing; Lü, Jinhu; Lin, Zhuosheng; Chen, Ping
Summary: This paper proposes a chaotic map‐based multicast scheme for multiuser speech wireless communication and implements it in an ARM platform. The scheme compresses the digital audio signal decoded by a sound card and then encrypts it with a three‐level chaotic encryption scheme. First, the position of every bit of the compressed data is permuted randomly with a pseudo‐random number sequence (PRNS) generated by a 6‐D chaotic map. Then, the obtained data are further permuted in the level of byte with a PRNS generated by a 7‐D chaotic map. Finally, it is operated with a multiround chaotic stream cipher. The whole system owns the following merits: the redundancy in the original audio file is reduced effectively and the corresponding unicity distance is increased; the balancing point between a high security level of the system and real‐time conduction speed is achieved well. In the ARM implementation, the framework of communication of multicast–multiuser in a subnet and the Internet Group Manage Protocol is adopted to obtain the function of communication between one client and other ones. Comprehensive test results were provided to show the feasibility and security performance of the whole system. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : To significantly reduce the audio's redundancy and increase the corresponding unicity distance, a chaotic map‐based multicast scheme is initiated for the multiuser speech wireless communication with ARM implementation. The working mechanism is summarized as two key steps: (i) compress the digital audio signal decoded by a sound card and (ii) encrypt the aforementioned signal by using a three‐level chaotic encryption scheme.